Development and performance evaluation of A 3-stage treatment system for domestic wastewater - Oon, Yin Wee. (Universiti Malaysia Sarawak (UNIMAS), 2008)
This research project focuses on the development and performance tests of a 3-stage domestic wastewater treatment system which consists of; 1) Spiral-Framed Human Hair-Based Filter (HBF), 2) Biotower (BT), and 3) Pistia Stratiotes-Based Free Water Surface System (FWS) for removal of oil and grease (O&G), suspended solids (SS), ammoniacal-nitrogen (NH3-N), biochemical oxygen demand (BODs) and nutrients such as nitrogen (N), phosphorous (P), and potassium(K) prior to discharge to natural waterway; The three primary components of the system operated in series. Domestic wastewaters were first induced to flow in a spiral pattern in the HBF for removal of O&G. The effluents from HBF were then trickled through the BT filled with perforated cylindrical plastic tubes to provide cross-flow alternated with vertical flow for removal ofSS, NH3-N, BODs and N. The final stage of the system was the FWS that focused on the removal of nutrients (N, P, K) by using a type of Sarawak local water lettuce called "Pistia Stratiotes". From this research, it was found that HBF achieved approximately . 73.54% removal of O&G, while the removal rates of BOD, NH3-N, N, P, K and SS by the biotower (TF) were approximately 35.0%, 57.4%, 51.8%, 13.4%, 21.8%, and 21.9%, respectively. The pollutant removal rates achieved by FWS were approximately 24.1 % BOD, 30.6% NH3-N, 38.0% N, 41.5% P, 46.7% K, and 37.1% SS. The overall combined removal efficiencies of HBF, BT and FWS were approximately 73.5%, 59.2%, 87.9%,90.6%, 54.9%, 68.5%, and 59.0% for O&G, BOD, NH3-N, N, P, K and SS, respectively.